2016
DOI: 10.5152/tjar.2016.79446
|View full text |Cite
|
Sign up to set email alerts
|

Mobbing Exposure of Anaesthesiology Residents in Turkey

Abstract: Objective: In recent years, psychological problems that are caused by working conditions like burn-out syndrome are more commonly observed. In our study, we aimed to evaluate mobbing exposure, factors causing mobbing and precautions for mobbing in residency students who are educated in anaesthesiology and reanimation clinics in Turkey. Methods:After obtaining consent from the ethics committee, we sent our questionnaires to the secretariats of the departments by postal mail. Completed questionnaires were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 9 publications
2
21
1
2
Order By: Relevance
“…Fourteen papers measured depression; eight found significant associations with bullying (Demir, Rodwell, & Flower, ; Ekici & Beder, ; Loerbroks et al., ; Nixon & Spector, ; Rodwell & Demir, ; Rugulies et al., ; Sá & Fleming, ; Yildirim, ), three did not comment on significance (Shabazz, Parry‐Smith, Oates, Henderson, & Mountfield, ; Vessey, Demarco, Gaffney, & Budin, ; Yildirim & Yildirim, ) and three found no significant association (Aykut et al., ; Pranjic, Males‐Bilic, Beganlic, & Mustajbegovic, ; Reknes et al., ). Of the papers which presented correlation coefficients, the strongest positive correlation was in a cross‐sectional study of 286 Turkish nurses; Pearson's product moment correlation r = 0.51 ( p < 0.001) (D. Yildirim, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen papers measured depression; eight found significant associations with bullying (Demir, Rodwell, & Flower, ; Ekici & Beder, ; Loerbroks et al., ; Nixon & Spector, ; Rodwell & Demir, ; Rugulies et al., ; Sá & Fleming, ; Yildirim, ), three did not comment on significance (Shabazz, Parry‐Smith, Oates, Henderson, & Mountfield, ; Vessey, Demarco, Gaffney, & Budin, ; Yildirim & Yildirim, ) and three found no significant association (Aykut et al., ; Pranjic, Males‐Bilic, Beganlic, & Mustajbegovic, ; Reknes et al., ). Of the papers which presented correlation coefficients, the strongest positive correlation was in a cross‐sectional study of 286 Turkish nurses; Pearson's product moment correlation r = 0.51 ( p < 0.001) (D. Yildirim, ).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven papers measured burnout, all of which found that bullying and burnout were significantly associated (Allen, Holland, & Reynolds, ; Aykut et al., ; Deery, Walsh, & Guest, ; Laschinger & Fida, ; Laschinger, Grau, Finegan, & Wilk, ; Laschinger, Grau, Finegan, & Wilk, ; Laschinger, Wong, & Grau, ; Read & Laschinger, ; Sá & Fleming, ; Trepanier, Fernet, & Austin, 2013a, ). Six papers used the subscales developed by Maslach et al., which measure burnout via ‘emotional exhaustion’ and ‘cynicism’ (Maslach, Schaufeli, & Leiter, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations